User interactivity in online newspapers: Exploring the relationship between content features and user response. (June 2019) - Riskos, Kyriakos; Dekoulou, Paraskevi; Tsourvakas, George
This study content analyzed 1, 050 online news articles, coming from five Greek online-only newspapers. Results indicate that hard content and news about global and political issues elicit more comments and replies. Readers share to their personal profiles on social networks more online articles about culture and articles that include videos and make more comments and replies on articles that contain hyperlinks. An in-depth analysis of articles about politics and global issues shows that articles about politics that contain infographics attract more comments and replies. The importance of interactivity for online news is highlighted.